Impact of technological innovation on corporate leverage in China: The moderating role of policy incentives and market competition - Ren, Lin; Liu, Dan; Xiong, Deping (Frontiers in Psychology, 2022)
Due to its capital-related nature, corporate leverage is highly exposed to financial risk, and optimising corporate leverage is an effective method of mitigating financial risk to maximise corporate value. We use a two-way fixed effects model to examine the impact of technological innovation on corporate leverage using panel data of A-share listed companies in the Chinese manufacturing sector from 2012 to 2020. Significant cross-sectional, spatial, and temporal dimensional heterogeneity characterises the relationship between technological innovation and corporate leverage. In addition, the findings suggest that both policy incentives and market competition have a dampening effect on the innovation-leverage relationship. The former has a policy effect known as "investment crowding out," while the latter has a market effect known as "innovation spillover." Furthermore, the eastern and western regions are negatively moderated by market competition and policy incentives, whereas the central region has no significant moderating effect. In general, this study provides empirical evidence for the rational allocation of resources by the Chinese government, the development of innovation capabilities, and the adjustment of leverage by firms from various regions.